The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/biof.1337
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin as a local therapeutic agent in cell therapy and tissue engineering

Abstract: Albumin is a major plasma protein that has become ubiquitous in regenerative medicine research. As such, many studies have examined its structure and advantageous properties. However, a systematic and comprehensive understanding of albumin's role, capabilities and therapeutic potential still eludes the field. In the present work, we review how albumin is applied in tissue engineering, including cell culture and storage, in vitro fertilization and transplantation. Furthermore, we discuss how albumin's physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 142 publications
(165 reference statements)
1
65
0
Order By: Relevance
“…With this in mind, the authors showed that serum albumin‐coated bone allograft (BoneAlbumin) successfully supports bone regeneration in various experimental models. The idea behind the phenomenon is that locally increased albumin concentration induces endogenous progenitor recruitment, resulting in the presence of a higher cell number to support the tissue remodelling phase (Horvathy, Simon, et al, ). Evidence of stem cell activation was supported by a first‐in‐human investigation, in which large albumin‐coated structural allografts were used to support recovery after total joint revision arthroplasty, with single photon emission computed tomography (SPECT) analysis showing increased osteoblast activation even 1 year after operation (Klara, Csonge, Janositz, Csernatony, & Lacza, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, the authors showed that serum albumin‐coated bone allograft (BoneAlbumin) successfully supports bone regeneration in various experimental models. The idea behind the phenomenon is that locally increased albumin concentration induces endogenous progenitor recruitment, resulting in the presence of a higher cell number to support the tissue remodelling phase (Horvathy, Simon, et al, ). Evidence of stem cell activation was supported by a first‐in‐human investigation, in which large albumin‐coated structural allografts were used to support recovery after total joint revision arthroplasty, with single photon emission computed tomography (SPECT) analysis showing increased osteoblast activation even 1 year after operation (Klara, Csonge, Janositz, Csernatony, & Lacza, ).…”
Section: Discussionmentioning
confidence: 99%
“…BoneAlbumin was also shown to decrease donor site morbidity and enhance bone formation after anterior cruciate ligament reconstruction with bone‐patellar tendon‐bone autografts (Schandl et al, ). Moreover, in a thorough review article, the albumin molecule was shown to have an important and potentially active but not yet completely understood role in bone regeneration (Horvathy, Simon, et al, ). Additionally, stem cell function was tested on various serum albumin‐coated surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is an advantageous preparation method to help in the application of an autologous biocompatible membrane for tissue regeneration. In the following experimental steps this membrane can be useful to start clinical studies to investigate the effect of frozen hypACT PRF membrane as gingival graft after bone replacing by albumin-coated bone granules in maxillofacial surgery [ 42 , 43 , 44 , 45 ], the material is also a promising candidate for clininal studies in orthopedics, namely in cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unavoidable to supplement cell cultures with serum-specific growth factors, and other, still-unidentified factors of the serum as MSCs cannot survive in the absence of such components. Thus, human blood-derived additives like human serum albumin (HSA) [ 12 ] or platelet releasates such as platelet-rich plasma (PRP) are considered as efficient alternatives to replace FCS [ 13 , 14 ]. The scientific rationale behind platelet-rich products is that thrombocytes provide a diverse growth factor supply such as platelet-derived growth factors (PDGFs), transforming growth factor beta-1 (TGF β -1) or vascular endothelial growth factor (VEGF), coagulation factors, serotonin, mitogens, and adhesion factors like fibronectin, fibrin, or vitronectin to support healing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%